THE APPLICATION OF ADVANCED TECHNOLOGIES FOR ENVIRONMENTAL PROTECTION - Mammadov, Elnur (Collection of scientific papers «ΛΌГOΣ», 2025)
The environmental impact of military operations has become an increasingly significant issue in modern warfare. Historically, military activities have been associated with extensive ecological damage, including the pollution of air, water, and soil, the destruction of natural habitats, and the depletion of critical resources. As global awareness of environmental sustainability grows, the need for the armed forces to adopt more eco-friendly and sustainable practices has never been more pressing. The concept of military ecology has emerged as a crucial aspect of modern defense strategies, aiming to mitigate the environmental footprint of military actions while maintaining operational effectiveness.